A survey of the clinical usage of intra-articular therapeutics in dogs by veterinary practitioners with a focus on non-steroidal therapies - Sepulveda, Camila P.; Corriveau, Kayla M.; Boone, Lindsey H.; Hofmeister, Erik H.; Kane, Margaret R.; Lascola, Kara M.; Wooldridge, Anne A. (Frontiers in Veterinary Science, 2026)
Osteoarthritis (OA) is a degenerative condition of the joint, whose progressive characteristics can lead to significant functional impairment and pain in the canine patient. Interest has increased regarding the use of intra-articular (IA) therapeutics as part of the multimodal management of canine OA. This study aimed to present the clinical experience of surgery and rehabilitation practitioners using these therapeutics to better understand their clinical usage, perceived outcomes, and clinical reasoning for product usage. A survey inquiring about IA injections with a focus on non-steroidal intra-articular therapeutics (NSIATs), including platelet-rich plasma (PRP), autologous conditioned serum (ACS), autologous protein solution (APS), cellular therapy, viscosupplements, and radionuclide, was distributed to canine practitioners. A total of 174 surveys were included in the results. Intra-articular injections were performed by 164 participants. Among these, 144 practitioners used NSIATs. The most common joint injected with steroidal and/or NSIATs was the elbow. The top reason for participants’ decision as to which NSIATs they preferentially used was scientific data and articles published regarding the product’s safety and efficacy. The most used NSIATs were PRP and viscosupplements, followed by cellular therapy, radionuclides, ACS, and APS. Practitioners reported that the most common reason to use NSIATs, except for APS, was chronic articular pathology needing ‘maintenance’ or routine injections. Pertaining to the top two most commonly used products, most participants did not combine PRP with other IA therapeutics. In the case of viscosupplements, 40% of the practitioners combined them with corticosteroids. According to the participants’ subjective assessment, most of the positive responders presented substantial or some clinical improvement after PRP or viscosupplements administration. As the first survey on this topic of small animal studies, these results provide valuable insights into the use of NSIATs in canines.